Dimensions of Animal Personalities in Guinea Pigs. (26th August 2013) - Zipser, Benjamin; Kaiser, Sylvia; Sachser, Norbert
Abstract: Behavioural phenotypes can be studied from a variety of perspectives. Recent developments have focused on the individual, seeking patterns of behaviour that are stable over time and/or across different contexts (animal personalities). This study applied this method of understanding individual behavioural variability to domestic guinea pigs. Two behavioural domains were investigated: emotionality and social behaviour. Additionally, individual cortisol–stress reactivity and dominance status were examined. Adult male domestic guinea pigs living in large mixed‐sex colonies were subjected to a series of behavioural and physiological tests twice with an intertest interval of 8 wk. Individual consistency over time was found regarding social behaviour, cortisol reactivity and dominance status, whereas no stability regarding emotional behaviour was detected. Furthermore, no stability over contexts was found. Our results suggest that the concept of animal personality is applicable to domestic guinea pigs. The ecological relevance of these data is underscored by the fact that they were obtained in animals from a very rich, socially complex scenario. Moreover, our study highlights that behaviour alone is not sufficient to describe individual phenotypic consistency. Physiological parameters such as stress reactivity should be included in animal personality research. Furthermore dominance – a relative measure which is not an absolute attribute of individuals – proved to be stable over time and thus also shed light on individuality.